Exercise Psychology - Buckworth Janet (Human Kinetics, 2002)
This book provides an in-depth examination of the relationships between exercise and psychological constructs, helping you to understand the thought processes behind the decision to exercise or not to exercise. Preface, Acknowledgements, Introduction and Basic Concepts, Foundations of Exercise Psychology, Basic Concepts in Exercise Psychology, Behavioral Neuroscience, Exercise and Mental Health, Stress, Affect and Mood and Emotion, Anxiety, Depression, Self-Esteem, Sleep, The Psychology of Physical Activity Behavior, Determinants of Exercise and Physical Activity, Theories of Behavior Change, Interventions to Change Physical Activity Behavior, Perceived Exertion, Glossary, Bibliography, Index.